Tail gas after-treatment three-way catalyst for motorcycle and preparation method of tail gas after-treatment three-way catalyst
By introducing a combination of perovskite composite molecular sieve and precious metal Pt-Rh coating into the motorcycle exhaust catalyst, the problem of insufficient low-temperature activity of the three-way catalytic converter for motorcycle exhaust has been solved, achieving the effects of efficient pollutant conversion and cost reduction at low temperatures.
Patent Information
- Application Number
- CN202511103317.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-07
- Publication Date
- 2025-11-18
AI Technical Summary
Motorcycle exhaust three-way catalysts have low pollutant conversion efficiency at low temperatures, high ignition temperature, and require a large amount of precious metals, making it difficult to meet strict emission standards and reduce costs.
A catalyst structure combining perovskite composite molecular sieve and noble metal Pt-Rh coating is adopted. By coating the catalyst support with Pd-containing perovskite composite molecular sieve coating and noble metal Pt-Rh coating, the low-temperature activity and HC conversion efficiency of the catalyst are improved, and the amount of noble metal used is reduced.
Improving the HC conversion efficiency of catalysts under low-temperature conditions, reducing ignition temperature, meeting stringent emission standards, while simultaneously reducing catalyst costs and improving catalyst durability and anti-aging properties.
Smart Images

Figure CN120961207A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of tail gas aftertreatment, and particularly relates to a tail gas aftertreatment three-way catalyst for a motorcycle and a preparation method thereof. BACKGROUND
[0002] The three-way catalyst (TWC) is an effective technical means for treating tail gas pollutants of gasoline vehicles such as motorcycles. The main active components of the TWC are Pt, Pd, Rh and other platinum group metals (PGM). The motor vehicle tail gas catalyst is the largest field of PGM consumption. In recent years, the number of motor vehicles has been increasing continuously, and the total demand for PGM has also increased sharply. Due to the scarcity of global PGM production, the price is very high. Therefore, it is necessary to reduce the use of PGM in the tail gas catalyst, especially for motorcycles, which are low-priced motor vehicles.
[0003] The motorcycle emission standard is continuously upgraded, and the proportion of cold start pollutants is increasing, so the TWC is required to have a lower light-off temperature. At present, the light-off temperature of the TWC is generally 250-400℃, and under the normal driving conditions of the motorcycle (the exhaust gas temperature of the engine is generally higher than 400℃), the TWC can effectively convert tail gas pollutants. However, when the motorcycle is started for the first time after a long period of parking, the temperature of the TWC is far below the active temperature, and it cannot effectively convert pollutants. In addition, with the improvement of engine design, more energy produced by in-cylinder combustion is converted into useful work, and the exhaust temperature during normal operation of the vehicle is reduced, making it more difficult to meet the current strict emission standards. Therefore, improving the low-temperature catalytic activity of the TWC is an important research topic in the field of tail gas purification catalysts.
[0004] Therefore, it is an urgent problem to be solved in the current motorcycle tail gas aftertreatment technology to seek a new catalyst material preparation method, reduce the light-off temperature of the catalyst, meet the emission requirements, and further reduce the amount of PGM to reduce the cost of the catalyst. SUMMARY
[0005] In view of the problems of low pollutant conversion efficiency and high light-off temperature of the current motorcycle three-way catalyst, the application provides a tail gas aftertreatment three-way catalyst for a motorcycle and a preparation method thereof. The perovskite composite molecular sieve is applied to the three-way catalyst to increase the conversion activity of HC pollutants, improve the conversion efficiency of the catalyst for HC, reduce the light-off temperature, and further reduce the amount of PGM to achieve the purpose of reducing the cost of the catalyst.
[0006] To achieve the above technical purposes, the technical solutions adopted by the embodiments of the application are as follows: In a first aspect, the embodiments of the application provide a tail gas aftertreatment three-way catalyst for a motorcycle, which comprises a catalyst carrier, and a Pd-containing perovskite composite molecular sieve coating layer and a noble metal Pt-Rh coating layer are sequentially coated on the catalyst carrier. The dry material components of the Pd-containing perovskite composite molecular sieve coating by mass percentage include: Pd 0.05% to 0.5%, perovskite 1% to 10%, molecular sieve 85% to 90%, and the balance of Al2O3; the dry material components of the noble metal Pt-Rh coating include: Pt 0.05% to 0.5%, Rh 0.05% to 0.5%, CeZrO2 25% to 50%, and the balance of Al2O3.
[0007] Further, the perovskite used in the Pd-containing perovskite composite molecular sieve coating is of the type of ABO3, wherein A is La and B is one or more of transition elements Fe, Co, Cu and Mn, and the molecular sieve used for compounding is one or more of MFI, CHA, BEA and LTA type molecular sieves.
[0008] Further, in the Pd-containing perovskite composite molecular sieve coating, the molar ratio of silicon to aluminum atoms of the molecular sieve is 15 to 150:1, and the mass of the transition element at the B site in the perovskite is 3% to 15% of the mass of the Pd-containing perovskite composite molecular sieve coating.
[0009] Further, the precursors of the noble metals Pt and Rh in the noble metal Pt-Rh coating, and the precursor of the noble metal Pd in the Pd-containing perovskite composite molecular sieve coating are nitrate.
[0010] Further, the Pd-containing perovskite composite molecular sieve coating and the noble metal Pt-Rh coating further contain a water locking agent and a tackifier; The water locking agent is one or more of sorbitol, polyvinyl alcohol and polyethylene glycol, and the amount is 0.1% to 0.5% of the total weight of the dry material components of each coating; The tackifier is one or more of hydroxyethyl cellulose, hydroxypropyl cellulose and carboxymethyl cellulose, and the amount is 0.25% to 0.75% of the total weight of the dry material components of each coating.
[0011] In a second aspect, the present application provides a preparation method of the motorcycle exhaust aftertreatment three-way catalyst according to the first aspect, including the following steps: (1) preparing slurry: weighing the dry material components, water locking agent and tackifier of each coating according to the corresponding mass percentage, and then respectively preparing noble metal Pt-Rh coating slurry and Pd-containing perovskite composite molecular sieve coating slurry for standby; The solid content of the Pd-containing perovskite composite molecular sieve coating slurry is 24wt% to 32wt%, and the solid content of the noble metal Pt-Rh coating slurry is 23wt% to 31wt%. (2) slurry coating: using coating machine according to the coating sequence of Pd-containing perovskite composite molecular sieve coating layer → noble metal Pt-Rh coating layer, the catalyst slurry is coated on the catalyst carrier in turn, and after coating each layer of slurry, a blast drier is used for drying and high-temperature calcination in a muffle furnace, and then the next layer is coated. After two layers of catalyst coating are completed, a low-temperature high-activity three-way catalyst is obtained.
[0012] Further, the process of preparing the slurry comprises the following steps: (1.1) Pd-containing perovskite composite molecular sieve coating slurry preparation: The dry components, water-retaining agent and tackifier of the Pd-containing perovskite composite molecular sieve coating layer are weighed according to the corresponding mass percentage; deionized water is added to the container, the molecular sieve to be compounded is added to the container and stirred for 30-60 min, palladium nitrate is added and stirred for 60-90 min; the perovskite slurry is added and stirred for 60-90 min; the pH is adjusted to 2.0-3.5; the Al2O3 binder is added and stirred for 60-90 min, the water-retaining agent is added and stirred for more than 30 min, and then the tackifier is added, and the stirring time is not less than 6 h, thereby obtaining the Pd-containing perovskite composite molecular sieve coating slurry; (1.2) noble metal Pt-Rh coating slurry preparation The dry components, water-retaining agent and tackifier of the noble metal Pt-Rh coating layer are weighed according to the corresponding mass percentage; deionized water is added to the container, then Al2O3 is added to the container and stirred for 30-60 min, CeZrO2 is added and stirred for 60-90 min, and then platinum nitrate and rhodium nitrate are added and stirred for not less than 1 h, wherein the addition time interval of platinum nitrate and rhodium nitrate is 20-40 min; the pH is adjusted to 2.0-3.5; then the water-retaining agent is added and stirred for 30-60 min, and then the tackifier is added, and the stirring time is not less than 6 h, thereby obtaining the noble metal Pt-Rh coating slurry.
[0013] Further, the process of slurry coating comprises the following steps: (2.1) Pd-containing perovskite composite molecular sieve coating slurry coating: The Pd-containing perovskite composite molecular sieve coating slurry is coated on one end of the catalyst carrier using a coating machine, and the coating height is 50%±5% of the total height of the catalyst carrier; after coating is completed, drying is performed using a blast drier, and the blast drier temperature is 180℃±10℃, and the drying time is 5-10 min; The catalyst carrier is turned over, and the Pd-containing perovskite composite molecular sieve coating slurry is coated on the other end of the catalyst carrier using a coating machine, and the coating height is 50%±5% of the total height of the catalyst carrier; after coating is completed, drying is performed using a blast drier, and the blast drier temperature is 180℃±10℃, and the drying time is 5-10 min; High-temperature calcination is carried out in a muffle furnace, and the parameters of the calcination furnace are set as follows: the first temperature rising interval is room temperature~200 DEG C, the temperature rising time is 30~60 min, the second temperature rising interval is 200~600 DEG C, the temperature rising time is 30~60 min, the third interval is a holding interval, the holding time is 60~90 min, and the calcination program is completed, and then the temperature is naturally reduced to room temperature; (2.2) noble metal Pt-Rh coating slurry coating The noble metal Pt-Rh coating slurry is coated on one end of the catalyst carrier using a coating special machine, and the coating height is 50%±5% of the total height of the catalyst carrier; after coating, drying is carried out using a blast drier, the blast drier temperature is 180 DEG C±10 DEG C, and the drying time is 5~10 min; The catalyst carrier is turned over, and the noble metal Pt-Rh coating slurry is coated on the other end of the catalyst carrier using a coating special machine, and the coating height is 50%±5% of the total height of the catalyst carrier; after coating, drying is carried out using a blast drier, the blast drier temperature is 180 DEG C±10 DEG C, and the drying time is 5~10 min; High-temperature calcination is carried out in a muffle furnace, and the parameters of the calcination furnace are set as follows: the first temperature rising interval is room temperature~200 DEG C, the temperature rising time is 30~60 min, the second temperature rising interval is 200~600 DEG C, the temperature rising time is 30~60 min, the third interval is a holding interval, the holding time is 60~90 min, and the calcination program is completed, and then the temperature is naturally reduced to room temperature; Further, the coating amount of the Pd-containing perovskite composite molecular sieve coating is 50~80 g / L based on the loading weight of the unit carrier; and the coating amount of the noble metal Pt-Rh coating is 50~80 g / L.
[0014] The technical scheme provided by the embodiment of the application has the following beneficial effects: (1) The perovskite composite molecular sieve is applied to the ternary catalyst in the application, the B site atom of the perovskite is a transition metal, Pd is easy to interact with the transition metal, and the orbitals between them are hybridized, so when the noble metal is doped into the perovskite crystal lattice, the catalytic activity of the perovskite is improved, the working temperature range of the catalyst is expanded, the HC conversion efficiency of the catalyst under the condition that the catalyst body temperature is low in the cold start stage of the engine is improved, the use amount of the noble metal Pd in the catalyst is reduced, and the purpose of reducing the cost is achieved.
[0015] (2) The perovskite composite molecular sieve and the noble metal Pd form a coating, which is convenient to coat; the mixed coating is located at the bottom layer of the catalyst, which not only improves the ignition effect, but also cooperates with the noble metal Pt-Rh to further reduce the HC emission in the tail gas, and ensures the tail gas purification effect. The tail gas reaching the perovskite composite molecular sieve catalyst has sufficient HC and oxygen to support the oxidation-reduction reaction of NOx and HC, ensure the reduction ability of the catalyst to NOx, and further eliminate NOx and HC in the tail gas, so that the content of the finally emitted pollutants is lower, and the national IV emission standard is met.
[0016] (3) The transition metal of the transition metal composite molecular sieve is Fe, Co, Cu, Mn or the like, when the transition metal in the perovskite and the molecular sieve are used as active components, the interaction occurs, the porous characteristics of the molecular sieve can limit the mutual agglomeration of the composite substances under high temperature conditions, and the dispersion effect is achieved while the transition element activity under high temperature conditions is inhibited, so that the catalytic ability of the catalyst is ensured, and the aging resistance of the catalyst is further improved.
[0017] (4) The catalyst increases the HC-SCR reaction path through the perovskite composite molecular sieve, increases the reaction activity on the basis of the original two-layer purification coating, achieves the purpose of reducing the amount of noble metal Pd in the catalyst while considering fuel consumption, improves the durability of the catalyst, and has superior catalytic effect, and is especially suitable for a metal honeycomb carrier with small volume for a motorcycle, and has good practical value and important economic value. BRIEF DESCRIPTION OF DRAWINGS
[0018] Figure 1 The figure is a curve diagram of the HC conversion effect of the catalyst in the examples 1-5 and the comparative examples of the present application. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be described clearly and completely in combination with examples. The medicines involved in the examples are all purchased in the market, and the purity of those without marked purity are all industrial grade or analytical grade.
[0020] Example 1 A motorcycle tail gas aftertreatment three-way catalyst, comprising a carrier, wherein the carrier is coated with a Pd-containing perovskite composite molecular sieve coating and a noble metal Pt-Rh coating in sequence. The perovskite used in the Pd-containing perovskite composite molecular sieve coating is LaCoO3, and the molecular sieve used for compounding is MFI type molecular sieve, which is used as the main effective component of the catalyst and as an active component coating together with the noble metal Pd, and is coated below the noble metal Pt-Rh coating, for improving the HC conversion efficiency of the catalyst and reducing the amount of noble metal Pd.
[0021] The preparation method of the motorcycle exhaust aftertreatment three-way catalyst comprises the following steps: (1) Prepare a catalyst coating slurry: (1.1) Preparation of Pd-containing perovskite composite molecular sieve coating slurry: Take LaCoO3 (AR) 120.5 g, MFI type molecular sieve 1060 g (manufacturer: Zhuoran Environmental Protection, model: ZSM-11), Al2O3 44.5 g, palladium nitrate (GR) 2.14 g (palladium 1.25 g), sorbitol 6.0 g, and hydroxypropyl cellulose 3.0 g. Add 3650 mL of deionized water to the container, add the MFI type molecular sieve to the container and stir for 35 min; add palladium nitrate and stir for 70 min, add LaCoO3 (AR) and stir for 90 min; adjust the pH to 3.5, then add Al2O3 and stir for 70 min; then add sorbitol and stir for 40 min, then add hydroxypropyl cellulose and stir for 6 h to obtain a Pd-containing perovskite composite molecular sieve coating slurry, the solid content of which is 25.3 wt%, ready for use.
[0022] (1.2) Preparation of noble metal Pt-Rh coating slurry: Take platinum nitrate (GR) 7.7 g (containing 4.5 g of platinum), rhodium nitrate (GR) 12.6 g (containing 4.5 g of rhodium), CeZrO2 455 g, Al2O3 440 g, sorbitol 4.5 g, and hydroxypropyl cellulose 6.5 g. Add 2050 mL of deionized water to the container, add Al2O3 to the container and stir for 40 min, add CeZrO2 and stir for 80 min; add platinum nitrate and palladium nitrate separately, with an interval of 30 min, and stir for 60 min; adjust the pH to 3.2; then add sorbitol and stir for 40 min, then add hydroxypropyl cellulose and stir for 6 h to obtain a noble metal Pt-Rh coating slurry, the solid content of which is 30.9 wt%, ready for use.
[0023] Then, the catalyst coating slurries are sequentially coated on the catalyst carrier, and the catalyst carrier has a specification of 52*120*101.5mm-300cpsi, and the coating process is as follows: (2.1) Coating of Pd-containing perovskite composite molecular sieve layer The Pd-containing perovskite composite molecular sieve layer slurry is coated on the gas inlet end of the catalyst carrier using a coating machine, the coating height is 55% of the inner wall height of the catalyst carrier, and the coating amount is 40 g / L. After coating, drying is performed using a blast drying machine, the drying machine temperature is 180°C, and the drying time is 10 min. After cooling, the catalyst carrier is turned over, the Pd-containing perovskite composite molecular sieve layer slurry is coated on the gas outlet end of the catalyst carrier using a coating machine, the coating height is 55% of the total height of the catalyst carrier, and the coating amount is 40 g / L. After coating, drying is performed using a blast drying machine, the drying machine temperature is 180°C, and the drying time is 10 min. Finally, high-temperature calcination is performed, and the calcination furnace parameters are set as follows: the first-stage temperature rising interval is room temperature-200°C, the temperature rising time is 30 min, the second-stage temperature rising interval is 200-600°C, the temperature rising time is 30 min, the third stage is a temperature holding interval, the temperature holding time is 90 min, and natural cooling to room temperature is performed after the calcination procedure is completed.
[0024] (2.2) Coating of a noble metal Pt-Rh layer The noble metal Pt-Rh layer slurry is coated on the gas inlet end of the catalyst carrier after step (2.1) calcination using a coating machine, the coating height is 55% of the inner wall height of the catalyst carrier, and the coating amount is 35 g / L. After coating, drying is performed using a blast drying machine, the drying machine temperature is 180°C, and the drying time is 10 min. After cooling, the catalyst carrier is turned over, the noble metal Pt-Rh layer slurry is coated on the gas outlet end of the catalyst carrier using a coating machine, the coating height is 55% of the total height of the catalyst carrier, and the coating amount is 35 g / L. After coating, drying is performed using a blast drying machine, the drying machine temperature is 180°C, and the drying time is 10 min. Finally, high-temperature calcination is performed, and the calcination furnace parameters are set as follows: the first-stage temperature rising interval is room temperature-200°C, the temperature rising time is 30 min, the second-stage temperature rising interval is 200-600°C, the temperature rising time is 30 min, the third stage is a temperature holding interval, the temperature holding time is 90 min, and natural cooling to room temperature is performed after the calcination procedure is completed.
[0025] After the two coatings are completed, a low-temperature high-activity three-way catalyst 1 (referred to as product 1) is obtained.
[0026] Example 2 A motorcycle exhaust aftertreatment three-way catalyst, the perovskite in the perovskite composite molecular sieve layer of the catalyst is LaFeO3, and the composite molecular sieve is MFI molecular sieve. The slurry preparation and coating process and related parameters of the catalyst are the same as those of Example 1, and a low-temperature high-activity three-way catalyst 2 (product 2) is obtained.
[0027] Example 3 A motorcycle exhaust aftertreatment three-way catalyst, the perovskite in the perovskite composite molecular sieve layer of the catalyst is LaMnO3, and the composite molecular sieve is MFI molecular sieve. The slurry preparation and coating process and related parameters of the catalyst are the same as those of Example 1, and a three-way catalyst 3 (product 3) with low temperature and high activity is obtained.
[0028] Example 4 A motorcycle exhaust aftertreatment three-way catalyst, the perovskite in the perovskite composite molecular sieve layer of the catalyst is LaCoO3, and the composite molecular sieve is CHA molecular sieve (manufacturer: Zel Catalysis, model: SSZ-13). The slurry preparation and coating process and parameters of the catalyst are the same as those of Example 1, and a three-way catalyst 4 (product 4) with low temperature and high activity is obtained.
[0029] Example 5 A motorcycle exhaust aftertreatment three-way catalyst, the perovskite in the perovskite composite molecular sieve layer of the catalyst is LaCoO3, and the composite molecular sieve is BEA molecular sieve (manufacturer: Hengxin Tian, model: Beta-25). The slurry preparation and coating process and parameters of the catalyst are the same as those of Example 1, and a three-way catalyst 5 (product 5) with low temperature and high activity is obtained.
[0030] Comparative Example 1 This example is to prepare a Pd-containing molecular sieve three-way catalyst, and the specific preparation process is as follows: (1) Take MFI type molecular sieve (manufacturer: Zhuoran Environmental Protection, model: ZSM-11) 1060g, Al2O344.5g, palladium nitrate (GR) 1.91g (palladium 1.115g), sorbitol 6g, hydroxypropyl cellulose 3.0g. Add deionized water 3290mL in the container, add MFI type molecular sieve into the container and stir for 35min; add palladium nitrate, stir for 70min, adjust pH=3.5, then add Al2O3 and stir for 70min; then add sorbitol and stir for 40min, then add hydroxypropyl cellulose and stir for 6h, to obtain a Pd-containing molecular sieve coating slurry, and the solid content is 25.3wt%, ready for use. The Pd-containing molecular sieve coating is coated as the Pd-containing perovskite composite molecular sieve layer in Example 1.
[0031] (2) The preparation and coating of the noble metal Pt-Rh layer are the same as those of Example 1. Finally, a Pd-containing molecular sieve three-way catalyst comparative product 1 (referred to as comparative product 1) is obtained.
[0032] The removal rates of HC, CO and NOx pollutants in the tail gas of the low-Pd type three-way catalyst products prepared in Examples 1-5 and Comparative Example 1 were detected, and the Pd content in the examples and comparative examples was the same, which was 0.1wt% of the dry component of the catalyst. At the same time, the durability test of each catalyst product was carried out. Specifically, the three-way catalyst products prepared in Examples 1-5 and Comparative Example 1 were respectively used as accessories of the tail gas treatment device of a certain type of China IV motorcycle (displacement 125mL), and were installed on the motorcycle for experiment to detect the pollutant treatment effect. The detection method refers to the provisions of the national standard GB 14622-2016 "Motorcycle Exhaust Emission Limits and Measurement Methods (China Stage IV)". Table 1: Detection results of the pollutant treatment ability of the catalyst products of Examples 1-5 and Comparative Example 1 on the motorcycle tail gas
[0033] From the detection results in Table 1, first, compared with the blank carrier, the catalysts of the present application Examples 1-5 can well remove the three pollutants of HC, CO and NOx in the tail gas; secondly, compared with the removal effect of Comparative Example 1, the perovskite composite molecular sieve layer in the catalyst of the present application has a further removal effect on the three pollutants of HC, CO and NOx; in addition, the removal effect of Example 1 on the three pollutants of HC, CO and NOx is better than that of Examples 2-5, which is because when the Co element in the perovskite and the molecular sieve are used as the bottom coating, they interact with each other, the multi-pore channel of the molecular sieve can provide a good confinement effect, after loading cobalt, it can limit the mutual aggregation of cobalt atoms under high temperature conditions, and at the same time it can inhibit the deactivation of cobalt element activity after high temperature, so as to ensure the selective catalytic reduction ability of the catalyst, and better catalytic effect can be achieved. It can be seen from the HC conversion rate curve of Comparative Example 1 and Examples 1-5 (see Figure 1) that the conversion rate of pollutants at high temperature in Comparative Example 1 also does not reach 100%, which further illustrates that the addition of perovskite helps to improve the activity of noble metal Pd, thereby reducing the light-off temperature of the coating to HC pollutants. Figure 1
[0034] Catalyst durability test: each catalyst product was worked with the vehicle, and was run on the motorcycle drum according to the regulation durability condition for 10000km (equivalent to 20000km mileage required by the regulation after multiplying the degradation number according to the regulation), and then the emission values of HC, CO and NOx were detected, and the detection results are shown in Table 2.
[0035] Table 2: Durability detection results of the pollutant treatment ability of each catalyst product on the tail gas
[0036] According to the detection results in Table 2, it can be concluded that, compared with the comparative product 1 without the perovskite composite molecular sieve catalyst, the catalysts of the present application can continuously remove the three pollutants well, and not only the HC emission value is within the limit value of the national IV emission standard, but also the CO and NOx meet the new regulation emission value limit requirements.
[0037] The treatment capacity of the perovskite composite molecular sieve catalyst with different Pd contents for HC, CO and NOx in the exhaust gas was investigated. The low-Pd type three-way catalyst prepared in Example 1 was used as the investigation basis, and the Pd content of the coating slurry of the Pd-containing perovskite composite molecular sieve was added in different mass percentages during the preparation of the catalysts in Examples 6-9. The Pd contents of the catalysts investigated are shown in Table 3, wherein the Pt and Rh noble metal contents are the same as in Example 1, and the other relevant parameters are the same as in Example 1. Each catalyst product was worked with the vehicle for 10,000 km durability according to the regulation working condition, and the detection method and results were the same as in Example 1. The detection results are shown in Table 4.
[0038] Table 3 Pd contents (wt%) of the catalysts in Examples 1, 6-9
[0039] Table 4 Detection results of the treatment capacity of the catalysts with different Pd contents for the pollutants in the motorcycle exhaust gas
[0040] As can be seen from the detection results in Table 4, if the Pd content in the perovskite composite molecular sieve catalyst is too low, the conversion rate of part of the pollutants is not enough, which can result in that the emission cannot meet the emission standard limit value of the national IV pollutants; and when the Pt and Rh noble metal contents are unchanged, with the increase of the coating amount of the Pd-containing perovskite composite molecular sieve catalyst, the removal effects of the catalyst for HC, CO and NOx are enhanced, so that under the premise of ensuring the ideal purification effect, the coating amount of the perovskite composite molecular sieve coating is controlled to a reasonable range, so as to achieve the optimal cost reduction and efficiency improvement purposes.
[0041] Overall, the catalyst of the present application increases the reaction path of HC conversion through the interaction between the transition metal in the perovskite and the molecular sieve, increases the reaction window on the basis of the original two-layer purification coating, achieves the purpose of reducing the amount of noble metal Pd in the catalyst while considering the fuel consumption, improves the catalyst durability mileage, and has superior catalytic effect, and can be used for vehicle purifiers of fuel vehicles, motorcycles and the like, and is particularly suitable for small-sized motorcycle metal honeycomb carriers, and has good practical value and important economic value.
[0042] It is apparent that for the skilled in the art, the present application is not limited to the details of the above exemplary embodiments, but can be implemented in other specific forms without departing from the spirit or essential characteristics of the present application. Therefore, the embodiments should be considered in all aspects as illustrative and non-restrictive. Moreover, it should be understood that although the present specification is described in terms of embodiments, it does not contain only one technical solution, and the manner of description of the specification is only for the sake of clarity, and the skilled in the art should consider the specification as a whole, and the technical solutions in the embodiments can also be appropriately combined to form other embodiments that can be understood by the skilled in the art.
[0043] Finally, it should be noted that the above specific embodiments are only used to illustrate the technical solutions of the present application and are not limiting. Although the present application is described in detail with reference to examples, those skilled in the art should understand that the technical solutions of the present application can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application, and they should be covered in the scope of the claims of the present application.
Claims
1. A motorcycle exhaust gas aftertreatment three-way catalyst comprising a catalyst carrier, characterized in that, The catalyst carrier is coated with a Pd-containing perovskite composite molecular sieve coating and a noble metal Pt-Rh coating in sequence; The dry material components of the Pd-containing perovskite composite molecular sieve coating include, in terms of mass percentage, Pd 0.05% to 0.5%, perovskite 1% to 10%, molecular sieve 85% to 90%, and the balance Al2O3; and the dry material components of the noble metal Pt-Rh coating include Pt 0.05% to 0.5%, Rh 0.05% to 0.5%, CeZrO2 25% to 50%, and the balance Al2O3.
2. The motorcycle exhaust gas aftertreatment three-way catalyst according to claim 1, characterized in that, The perovskite used in the Pd-containing perovskite composite molecular sieve coating is of the type ABO3, wherein A is La and B is one or more of transition elements Fe, Co, Cu and Mn; and the molecular sieve used in the composite perovskite is one or more of MFI, CHA, BEA and LTA type molecular sieves.
3. The motorcycle exhaust gas aftertreatment three-way catalyst according to claim 2, characterized in that In the Pd-containing perovskite composite molecular sieve coating, the molar ratio of silicon to aluminum of the molecular sieve is 15 to 150:1, and the mass of the transition element at the B site in the perovskite is 3% to 15% of the mass of the Pd-containing perovskite composite molecular sieve coating.
4. The motorcycle exhaust gas aftertreatment three-way catalyst according to claim 1, characterized in that, The precursors of the noble metals Pt and Rh in the noble metal Pt-Rh coating and the precursor of the noble metal Pd in the Pd-containing perovskite composite molecular sieve coating are nitrate.
5. The motorcycle exhaust gas aftertreatment three-way catalyst according to claim 1, characterized in that, The Pd-containing perovskite composite molecular sieve coating and the noble metal Pt-Rh coating further contain a water locking agent and a tackifier; The water locking agent is one or more of sorbitol, polyvinyl alcohol and polyethylene glycol, and the amount used is 0.1% to 0.5% of the total weight of the dry material components of the coating; The tackifier is one or more of hydroxyethyl cellulose, hydroxypropyl cellulose and carboxymethyl cellulose, and the amount used is 0.25% to 0.75% of the total weight of the dry material components of the coating.
6. The method for producing a motorcycle exhaust gas aftertreatment three-way catalyst according to any one of claims 1 to 5, characterized by, The method comprises the following steps: (1) Preparing a slurry: the dry material components, water locking agent and tackifier of each coating are weighed according to the corresponding mass percentage, and then noble metal Pt-Rh coating slurry and Pd-containing perovskite composite molecular sieve coating slurry are prepared respectively and kept ready for use; The solid content of the Pd-containing perovskite composite molecular sieve coating slurry is 24% to 32%, and the solid content of the noble metal Pt-Rh coating slurry is 23% to 31%; (2) Slurry coating: using a coating special machine, the catalyst slurry is coated on the catalyst carrier in the order of Pd-containing perovskite composite molecular sieve coating→noble metal Pt-Rh coating, and after each layer of slurry is coated, a blast drier is used for drying and a muffle furnace is used for high-temperature calcination before the next layer is coated, and after the two layers of catalyst are coated, a low-temperature high-activity three-way catalyst is obtained.
7. The method of producing a motorcycle exhaust gas aftertreatment three-way catalyst according to claim 6, characterized by, The process of preparing the slurry comprises the following steps: (1.1) Preparation of Pd-containing perovskite composite molecular sieve coating slurry: The dry material components, water locking agent and tackifier of the Pd-containing perovskite composite molecular sieve coating are weighed according to the corresponding mass percentage; deionized water is added to a container, the molecular sieve to be compounded is added to the container and stirred for 30-60 min, palladium nitrate is added and stirred for 60-90 min; perovskite is added and stirred for 60-90 min; the pH is adjusted to 2.0-3.5; Al2O3 is added and stirred for 60-90 min, the water locking agent is added and stirred for more than 30 min, and then the tackifier is added, and the stirring time is not less than 6 h, thereby obtaining the Pd-containing perovskite composite molecular sieve coating slurry; (1.2) Preparation of noble metal Pt-Rh coating slurry The dry material components and water locking agent and tackifier of the noble metal Pt-Rh coating are weighed according to the corresponding mass percentage; deionized water is added to a container, then Al2O3 is added to the container and stirred for 30-60 min, CeZrO2 is added and stirred for 60-90 min, and then platinum nitrate and rhodium nitrate are added and stirred for not less than 1 h, wherein the addition time interval of platinum nitrate and rhodium nitrate is 20-40 min; the pH is adjusted to 2.0-3.5; then the water locking agent is added and stirred for 30-60 min, and then the tackifier is added and stirred for not less than 6 h, thereby obtaining the noble metal Pt-Rh coating slurry.
8. The method of producing a motorcycle exhaust gas aftertreatment three-way catalyst according to claim 6, characterized by, The slurry coating process includes the following steps: (2.1) Pd-containing perovskite composite molecular sieve coating slurry coating: The Pd-containing perovskite composite molecular sieve coating slurry is coated on one end of the catalyst carrier using a coating machine, and the coating height is 50%±5% of the total height of the catalyst carrier; after coating, drying is performed using a blast drying machine, the blast drying machine temperature is 180±10℃, and the drying time is 5-10 min; The catalyst carrier is turned over, and the Pd-containing perovskite composite molecular sieve coating slurry is coated on the other end of the catalyst carrier using a coating machine, and the coating height is 50%±5% of the total height of the catalyst carrier; after coating, drying is performed using a blast drying machine, the blast drying machine temperature is 180±10℃, and the drying time is 5-10 min; High-temperature calcination is performed in a muffle furnace, and the muffle furnace parameters are set as follows: the first-stage temperature rising interval is room temperature-200℃, the temperature rising time is 30-60 min, the second-stage temperature rising interval is 200-600℃, the temperature rising time is 30-60 min, the third stage is a holding interval, and the holding time is 60-90 min; after the calcination program is completed, natural cooling to room temperature is performed; (2.2) Noble metal Pt-Rh coating slurry coating The noble metal Pt-Rh coating slurry is coated on one end of the catalyst carrier in step (2.1) using a coating machine, and the coating height is 50%±5% of the total height of the catalyst carrier; after coating, drying is performed using a blast drying machine, the blast drying machine temperature is 180±10℃, and the drying time is 5-10 min; The catalyst carrier is turned over, and a noble metal Pt-Rh coating slurry is coated on the other end of the catalyst carrier by using a coating special machine, and the coating height is 50%±5% of the total height of the catalyst carrier; after the coating is completed, drying is performed by using a blast drier, the blast drier temperature is 180±10°C, and the drying time is 5-10 min; High-temperature calcination is performed in a muffle furnace, and the furnace parameter settings are as follows: the first-stage temperature rising interval is room temperature-200°C, the temperature rising time is 30-60 min, the second-stage temperature rising interval is 200-600°C, the temperature rising time is 30-60 min, the third stage is a holding interval, and the holding time is 60-90 min; and after the calcination procedure is completed, natural cooling to room temperature is performed.
9. The method of producing a motorcycle exhaust gas aftertreatment three-way catalyst according to claim 6, characterized by, The coating amount of the Pd-containing perovskite composite molecular sieve coating is 50-80 g / L, and the coating amount of the noble metal Pt-Rh coating is 50-80 g / L, based on the unit carrier loading.